Needs Analysis of Secondary Students Studying in Government Schools in Bhavnagar District with Special Reference to Writing Skill - Bhavin Mahida; Dr. C.R. Gurjar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The significance of English today is very well known. It has become a world language due to its influence across different spheres of life. The demand of English language in a state like Gujarat is very high due to its ability to give an advantage it gives to students in education and in the work place the work place. Therefore, many initiatives been taken by the State governments to improve the standard of English. The textbooks prescribed by the State Board been made more interactive. However, there are many challenges due to which the aim has not been fulfilled. Many students especially in the rural regions of Gujarat still do not have even the basic competency required to progress to the next level. This study aims to understands the need of such learners.